KONTRIBUSI PERMAINAN DALAM MEDIA AUDIO VISUAL DI MASA PAMDEMI PADA PESERTA DIDIK. - Loisa, Irena; Triansyah, Andika; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The problem the researcher wants to uncover and find is to find out theContribution of Traditional Games in Audio Visual Media During thePandemic for Students of Santo Benedict Pahauman Middle School.The purpose of this research is where the researcher wants to revealand find that to find out the Contribution of Traditional Games inAudio Visual Media During the Pandemic. This research is aquantitative descriptive research, meaning that it is a research that isused to find out the actual situation based on the results of a valid andreliable questionnaire instrument and a survey method. Answers fromrespondents can be made with the highest score of "one" and the lowestscore of zero for the alternative answers in the drafting questionnaire,assigning a category for each positive statement yes = 1 and no = 0,while the category for each negative answer is yes = 0 and no = 1 inthe collation research using guttman scale in the form of a checklist.So it can be concluded that based on the results of data analysis anddiscussion of students totaling 60 answered yes 1,985 with apercentage of 98% and answered no 24 with a percentage of 2% of the34 questionnaire items.